Understanding and targeting cancer stem cells： therapeutic implications and challenges - Chen, Ke; Huang, Ying-hui; Chen, Ji-long (Acta pharmacologica Sinica, 2013)
Cancer stem cells （CSCs） have been identified as rare cell populations in many cancers, including leukemia and solid tumors. Accumulating evidence has suggested that CSCs are capable of self-renewal and differentiation into various types of cancer cells. Aberrant regulation of gene expression and some signaling pathways has been observed in CSCs compared to other tumor cells. CSCs are thought to be responsible for cancer initiation, progression, metastasis, recurrence and drug resistance. The CSC hypothesis has recently attracted much attention due to the potential for discovery and development of CSC-related therapies and the identification of key molecules involved in controlling the unique properties of CSC populations. Over the past several years, a tremendous amount of effort has been invested in the development of new drugs, such as nanomedicines, that can take advantage of the ＂Achilles＇ heel＂ of CSCs by targeting cell-surface molecular markers or various signaling pathways. Novel compounds and therapeutic strategies that selectively target CSCs have been identified, some of which have been evaluated in preclinical and clinical studies. In this article, we review new findings related to the investigation of the CSC hypothesis, and discuss the crucial pathways involved in regulating the development of CSC populations and the advances in studies of drug resistance. In addition, we review new CSC-targeted therapeutic strategies aiming to eradicate malignancies.